2003
DOI: 10.1055/s-2003-37773
|View full text |Cite
|
Sign up to set email alerts
|

Integration von Vorerkrankungen und Risikofaktoren im Abbreviated Burn Severity Index (ABSI)

Abstract: The results of this study show that the Abbreviated Burn Severity Index is an appropriate burn score for estimating the risk of mortality after burn trauma. However, in addition to the classical variables, preexisting diseases and risk factors have a significant influence on the outcome and therefore should be incorporated into a new burn score to predict mortality more accurately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 11 publications
0
11
0
2
Order By: Relevance
“…Different studies, for instance, have reported that cardiovascular disease is not associated with increased mortality, 7,8 predicts mortality on a univariate, but not a multivariate, basis, 9 or predicts mortality even after controlling for burn-related risk factors. 10,11 Findings on the effects of renal disease, 10,11 neurologic disease, 7,10,11 and chronic pulmonary disease 8,9 are similarly discrepant. In addition, the effects on mortality and length of stay of a number of potentially important comorbid conditions, including liver disease, obesity, hypertension, and cancer, have not been examined in burn patients.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Different studies, for instance, have reported that cardiovascular disease is not associated with increased mortality, 7,8 predicts mortality on a univariate, but not a multivariate, basis, 9 or predicts mortality even after controlling for burn-related risk factors. 10,11 Findings on the effects of renal disease, 10,11 neurologic disease, 7,10,11 and chronic pulmonary disease 8,9 are similarly discrepant. In addition, the effects on mortality and length of stay of a number of potentially important comorbid conditions, including liver disease, obesity, hypertension, and cancer, have not been examined in burn patients.…”
mentioning
confidence: 99%
“…They have also been limited by the lack of clearly defined comorbidity categories and diagnoses and, in most cases, by univariate analyses that do not control for important confounders, such as age. As a result, studies of the impact of the number of preexisting medical conditions on outcome 4 -7 or of the effects of specific medical comorbidities on outcome [7][8][9][10][11] have produced contradictory results. Different studies, for instance, have reported that cardiovascular disease is not associated with increased mortality, 7,8 predicts mortality on a univariate, but not a multivariate, basis, 9 or predicts mortality even after controlling for burn-related risk factors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, those studies were done on a smaller population and didn't adequately weigh the contribution of comorbidities on burn mortality. [17][18][19][20][21][22] A larger 2007 study was done by Thombs et al [23] looked at the effect of various comorbidities on burn injury mortality based on the National Burn Repository (NBR) report on 31,338 burn records from 1995-2005. They found that various pre-existing medical conditions, using the Charlson Comorbidity index and Elixhauser method of comorbidity measurement, affected burn mortality.…”
Section: Discussionmentioning
confidence: 99%
“…1). Faktoren wie Alkohol-und Nikotinabusus werden nicht berücksichtigt, die Erfahrung großer Verbrennungszentren jedoch zeigt auch in diesen Fällen eine erhebliche Verschlechterung der Überlebens-prognose [10,13].…”
Section: Abb 2 ▲ Strommarke Am Großzehunclassified